Chemical composition and antioxidant activity of noble yarrow (Achillea nobilis L. subsp. neilreichii (Kerner) Velen.) - Radovanović, Katarina; Hitl, Maja; Božin, Biljana; Bijelić, Katarina; Prpa, Blagoje; Aćimović, Milica; Gavarić, Neda (Archives of Pharmacy, 2022)
Species of the genus Achillea are well-known ancient medicinal plants. Noble yarrow is presented in eastern Serbia, Suva planina and Kosovo (around Peja). Due to the traditional use, it is important to determine the chemical composition and biological activities of these species widespread in Serbia. The aim of this study was to determine the chemical composition and antioxidant activity of noble yarrow. The content of total phenols in the prepared infusion was determined by the Folin – Ciocalteu method. Total flavonoids were determined spectrophotometrically by forming complexes with AlCl3. Chemical characterization was performed by high performance liquid chromatography. The antioxidant activity was examined spectrophotometrically by determining the "scavenger" activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl (OH •) radical and nitroso (NO •) radical, as well as redox potential testing by FRAP test and determination of inhibition lipid peroxidation in the Fe2 + / H2O2 induction system. The total phenol content in the tested infusion was 33.52 mg of gallic acid equivalent per gram of dry extract, while the content of total flavonoids was 6.79 mg of quercetin equivalent per gram of dry extract. Phenolic acids are dominantly presented in the infusion. Rosmarinic and p-coumaric acids are the most abundant (13.34 and 12.74 mg/g of dry extract). The infusion showed the ability to neutralize free radicals at medium high concentrations. Unlike the results of other antioxidant tests, inhibition of lipid peroxidation was not achieved. The tested plant is a good source of phenolic compounds with established antioxidant activity.